Prostitutes and transmission of AIDS/HIV implications on disease control management - Conaco, Maria Cecilia Gastardo (1992)
The mounting number of reported AIDS cases in the Philippines cannot be neglected nor ignored. This is largely due to hetero- and homosexual contact prevalent among hospitality girls, especially in areas where foreigners abound, such as Angeles and Subic where the military bases were used to be situated. In this study where 225 hospitality girls were interviewed, a positive correlation was derived between knowledge and awareness of condoms and its use, the latter being one of the several preventive measures in AIDS /HIV transmission. This therefore, calls for strict government intervention in providing proper and effective channels through which information on AIDS and its transmission can be adequately disseminated.
Keywords: AIDS Statistics; AIDS risk factors; AIDS epimediology; AIDS prevention; HIV (Viruses)